Protein supplements: Do they alter dietary intakes? - Mallard, A. R.; McLay-Cooke, R. T.; Rehrer, N. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Effects of protein versus mixed macronutrient supplementation on total energy intake (TEI) and protein intake during an ad libitum diet were examined. Trained males undertook two, 2-week dietary interventions which were randomized, double blinded, and separated by 2 weeks. These were high-protein supplementation (HP: 1034.5 kJ energy, 29.6 g protein, 8.7 g fat and 12.3 g CHO) and standard meal supplementation (SM: 1039 kJ energy, 9.9 g protein, 9.5 g fat, and 29.4 g CHO) consumed daily following a week of baseline measures. Eighteen participants finished both interventions and one only completed HP. TEI (mean ± SD) was not different between baseline (11148 ± 3347 kJ) and HP (10705 ± 3143 kJ) nor between baseline and SM (12381 ± 3877 kJ), however, TEI was greater with SM than HP (923 ± 4015 kJ p = .043). Protein intake (%TEI) was greater with HP (22.4 ±6.2%) than baseline (19.4 ± 5.4%; p = .008) but not SM (20.0 ± 5.0%). No differences in absolute daily protein intake were found. Absolute CHO intake was greater with SM than HP (52.0 ± 89.5 g, p = .006). No differences in fat intake were found. Body mass did not change between baseline (82.7 ± 11.2 kg) and either HP (83.1 ± 11.7 kg) or SM (82.9 ± 11.0 kg). Protein supplementation increases the relative proportion of protein in the diet, but doesn`t increase the absolute amount of total protein or energy consumed. Thus some compensation by a reduction in other foods occurs. This is in contrast to a mixed nutrient supple- ment, which does not alter the proportion of protein consumed but does increase TEI.